2018
DOI: 10.1111/jnc.14561
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and electronic cigarette (E‐Cig) exposure decreases brain glucose utilization in ischemic stroke

Abstract: Previous studies in our laboratory have shown that nicotine exposure decreases glucose transport across the blood-brain barrier in ischemia-reperfusion conditions. We hypothesize that nicotine can also dysregulate brain parenchymal glucose utilization by altering glucose transporters with effects on sensitivity to ischemic stroke. In this study, we investigated the effects of nicotine exposure on neuronal glucose utilization using an in vitro ischemic stroke model. We also tested the effects of e-Cig vaping on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 67 publications
3
53
0
1
Order By: Relevance
“…There have been reports of adverse health effects of e‐Cig use including enhanced carcinogenic potential (Lee et al, ), oxidative stress and inflammatory activity (Muthumalage et al, ), as well as altered BBB permeability and worsened ischemic brain injury (Kaisar, Villalba, et al, ). We have previously published that e‐Cig exposure can also decrease brain glucose utilization in ischemic stroke (Sifat et al, ). Among the general population, a group of people who can be drastically affected by the e‐Cig are pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There have been reports of adverse health effects of e‐Cig use including enhanced carcinogenic potential (Lee et al, ), oxidative stress and inflammatory activity (Muthumalage et al, ), as well as altered BBB permeability and worsened ischemic brain injury (Kaisar, Villalba, et al, ). We have previously published that e‐Cig exposure can also decrease brain glucose utilization in ischemic stroke (Sifat et al, ). Among the general population, a group of people who can be drastically affected by the e‐Cig are pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of neonatal HI brain injury was found to be inversely correlated with total brain glucose metabolism in a clinical study (Thorngren‐Jerneck et al, ). Previously we have reported that nicotine and e‐Cig exposure decreases brain glucose utilization in ischemic stroke (Sifat et al, ). But, till date, no study has been done to investigate the effects of prenatal e‐Cig exposure on offspring brain glucose utilization and the glucose transporters expression after neonatal HI brain injury.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations